2013
DOI: 10.1002/jbmr.1955
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gene polymorphisms can improve prediction of nonvertebral fracture in postmenopausal women

Abstract: Clinical risk factors (CRFs), with or without bone mineral density (BMD), are used to determine the risk of osteoporotic fracture (OF), which has a heritable component. In this study we investigated whether genetic profiling can additionally improve the ability to predict OF. Using 1229 unrelated Korean postmenopausal women, 39 single-nucleotide polymorphisms (SNPs) in 30 human genomic loci were tested for association with osteoporosis-related traits, such as BMD, osteoporosis, vertebral fracture (VF), nonvert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Although the set of SNPs used in the study was different from the present study's, the observed magnitude of association between GRS and fracture is consistent with the present study. Two empirical studies in postmenopausal women of Korean background also found that a genetic profiling of 39 SNPs in 30 human genomic loci could increase the precision of nonvertebral fracture prediction and help to define the risk threshold, whereas 35 risk alleles were significantly associated with the risk of vertebral fracture in patients on bisphosphonate. Taken together, these results and the present finding suggest that genetic profiling is useful in the identification of high‐risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the set of SNPs used in the study was different from the present study's, the observed magnitude of association between GRS and fracture is consistent with the present study. Two empirical studies in postmenopausal women of Korean background also found that a genetic profiling of 39 SNPs in 30 human genomic loci could increase the precision of nonvertebral fracture prediction and help to define the risk threshold, whereas 35 risk alleles were significantly associated with the risk of vertebral fracture in patients on bisphosphonate. Taken together, these results and the present finding suggest that genetic profiling is useful in the identification of high‐risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that including GRS as a predictor may help improve the accuracy of various fracture prediction models. For example, GRS of 39 SNPs increased the precision of non-vertebral fracture prediction in postmenopausal Korean women [31]. Additionally, GRS based on 63 SNPs improved the accuracy of non-trauma fracture prediction [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, after BMD adjustment, the effect sizes for these associations were substantially reduced, and they concluded that, when BMD is known, the clinical utility of the two GRSs for fracture prediction is limited in elderly subjects. Lee et al (2013) developed a GRS including 21 SNPs in 19 osteoporosis-susceptibility genes, and demonstrated that adding the GRS to the prediction model consisting of clinical risk factors and BMD could improve its predictive ability for non-vertebral fracture in 1229 unrelated Korean postmenopausal women. Lee et al (2016) also calculated the Korean-specific GRS from 35 SNPs associated with osteoporosis-related traits (GRS35), and found that integration of the GRS35 into the current model further improved its predictability for future osteoporotic fracture occurrence in a 6-year follow-up observational study.…”
Section: Discussionmentioning
confidence: 99%